Women in Plato’s Political Theory - Buchan, M. author. aut Link
VII, 189 p.
Keywords: Women in Plato's Political Theory argues that Plato's philosophy is a gendered philosophy; it contains within its basic tenets notions associated with masculinity. Consequently, the book explores the reasons why, in The Republic Plato includes women in the ruling class of his proposed ideal State on apparently equal terms with men and appears to offer them the opportunity to become Philosopher Kings, the ultimate rulers.